Exercises to improve the effectiveness of Tokui-Waza in Tachi Waza/Ejercicios para mejorar la efectividad del Tokui-Waza en el Tachi Waza - Teobaldo Martínez Perdomo; Lázaro Alberto Pastor Chirino; Osviel Hernández Sotolongo; Rosa María Tabares Arevalo; Esteban Eddy Méndes Lazo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2021)
In the current sport of Judo, the mastery of the Tokui-Waza or favorite technique is essential to defeat the opponent and win the victory, however this requires an adequate technical-tactical preparation and its systematization in the training process. From the existence of a series of inadequacies related to the didactic procedure of the coaches for the teaching-learning of the technical-tactical actions of Tokui Waza, in order to enable the athletes an adequate training in the process of technical preparation, based on new and better ways to address and improve this process, the objective of this research is to implement a set of exercises to improve the effectiveness of Tokui Waza in the Tachi Waza of the women's Judo team, category 15-16 years old, of the Integral Sports School in Pinar del Río, in correspondence with the different manifestations within the combat. For this purpose, a sample of 12 athletes, members of this team, was used. Scientific research methods and techniques were used, such as: observation, standardized and individual interview, as well as document analysis. As a result, a set of structured exercises is provided, which include simplified and complex situations, which act didactically on the components of the technical-tactical preparation, constituting a useful tool for coaches in the improvement of their work in the sports preparation of athletes.